Burnout and posttraumatic stress in paediatric critical care personnel: Prediction from resilience and coping styles. Issue 1 (January 2019) - Rodríguez-Rey, Rocío; Palacios, Alba; Alonso-Tapia, Jesús; Pérez, Elena; Álvarez, Elena; Coca, Ana; Mencía, Santiago; Marcos, Ana; Mayordomo-Colunga, Juan; Fernández, Francisco; Gómez, Fernando; Cruz, Jaime; et al.
Abstract: Introduction: Our aims were (1) to explore the prevalence of burnout syndrome (BOS) and posttraumatic stress disorder (PTSD) in a sample of Spanish staff working in the paediatric intensive care unit (PICU) and compare these rates with a sample of general paediatric staff and (2) to explore how resilience, coping strategies, and professional and demographic variables influence BOS and PTSD. Materials and Methods: This is a multicentre, cross-sectional study. Data were collected in the PICU and in other paediatric wards of nine hospitals. Participants consisted of 298 PICU staff members (57 physicians, 177 nurses, and 64 nursing assistants) and 189 professionals working in non-critical paediatric units (53 physicians, 104 nurses, and 32 nursing assistants). They completed the Brief Resilience Scale, the Coping Strategies Questionnaire for healthcare providers, the Maslach Burnout Inventory, and the Trauma Screening Questionnaire. Results: Fifty-six percent of PICU working staff reported burnout in at least one dimension (36.20% scored over the cut-off for emotional exhaustion, 27.20% for depersonalisation, and 20.10% for low personal accomplishment), and 20.1% reported PTSD. There were no differences in burnout and PTSD scores between PICU and non-PICU staff members, either among physicians, nurses, or nursing assistants. Higher burnout and PTSD rates emerged after the death of a child and/or conflicts with patients/families or colleagues. Around 30% of the variance in BOS and PTSD is predicted by a frequent usage of the emotion-focused coping style and an infrequent usage of the problem-focused coping style. Discussion and Conclusions: Interventions to prevent and treat distress among paediatric staff members are needed and should be focused on: (i) promoting active emotional processing of traumatic events and encouraging positive thinking; (ii) developing a sense of detached concern; (iii) improving the ability to solve interpersonal conflicts, and (iv) providing adequate training in end-of-life care.